2020
DOI: 10.3389/fmed.2020.621005
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Liver Involvement in Patients With Adult-Onset Still's Disease: Prevalence, Characteristics and Impact on Prognosis

Abstract: Objective: Adult-onset Still's disease (AOSD) is a systemic disorder commonly accompanied by liver involvement. This study aims to illustrate the detailed information of liver abnormalities in patients with AOSD and evaluate the impact on the prognosis.Methods: A total number of 128 hospitalized patients, who met the Yamaguchi criteria of AOSD in the Department of Rheumatology and Immunology, Ruijin Hospital from July 2016 to August 2019 were consecutively enrolled and followed up. The demographic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Secondary hemophagocytic lymphohistiocytosis, also known as macrophage activation syndrome, is the most severe complication associated with high mortality. Its common complications include coagulopathy with multiorgan involvement, including the heart, lung, liver, spleen, and other sites [ 17 , 18 ], and these patients often require more intensive treatment and have a worse prognosis. It has been shown that more than 20% of patients with AOSD experience recurrence and that patients with severe disease at the initial stage of the disease may be at an increased risk of recurrence, which requires intensive treatment and close follow-up [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary hemophagocytic lymphohistiocytosis, also known as macrophage activation syndrome, is the most severe complication associated with high mortality. Its common complications include coagulopathy with multiorgan involvement, including the heart, lung, liver, spleen, and other sites [ 17 , 18 ], and these patients often require more intensive treatment and have a worse prognosis. It has been shown that more than 20% of patients with AOSD experience recurrence and that patients with severe disease at the initial stage of the disease may be at an increased risk of recurrence, which requires intensive treatment and close follow-up [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these criteria can be employed to ascertain the clinical diagnosis of AOSD made by an expert [10,85,119] (see recommendation 2 in . Table 1 [44,55,100,174,177] (see recommendation 3 in . Table 1).…”
Section: Overarching Principles Statements and Recommendationsmentioning
confidence: 99%
“…38 Furthermore, serum prealbumin and albumin levels have been recently reported to be correlated with liver involvement and to negatively reflect the disease activity of patients, possibly as part of the acute phase response. 38 However, a more severe involvement with substantial cytolysis and hepatic necrosis may occur in connection with a multiorgan failure syndrome. 38,39 Although liver involvement is frequently observed in Still disease, it is quite heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, a more severe involvement with substantial cytolysis and hepatic necrosis may occur in connection with a multiorgan failure syndrome. 38,39 Although liver involvement is frequently observed in Still disease, it is quite heterogeneous. Nonspecific histopathologic changes of liver involvement may be observed also featuring hemophagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation